2014
DOI: 10.1002/app.41500
|View full text |Cite
|
Sign up to set email alerts
|

Transparent and durable SiO2‐containing superhydrophobic coatings on glass

Abstract: We fabricated novel superhydrophobic coatings based on SiO 2 nanoparticles combined with NH 2 -terminated silicone (SN 2 ) or SN 2 -modified polyurethane (SN 2 -prePU) by alternately spin-coating them onto glass slides. The final fabricated surface contained SN 2 /SiO 2 or SN 2 -prePU/SiO 2 bilayers. The conditions of spin-coating method were also explored. SN 2 -prePU with different SN 2 /prePU molar ratios were synthesized to study the influence of SN 2 ratio on the water contact angles of ultimate spin-coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…[1][2][3] Due to excellent self-cleaning effect, the ideal superhydrophobic surfaces with an extremely low sliding angle (SA) inspired by lotus leaf have attracted increasing attention for both fundamental research and practical applications. [4][5][6][7][8] However, some novel superhydrophobic surfaces in nature with high water adhesion, such as gecko feet, rose petals, scallions, and garlic, [9][10][11][12] have recently also attracted wide scientific interest because of their most outstanding application in no-loss microdroplet transportation known as a mechanical hand. [13][14][15][16] Especially, Jiang et al demonstrated a "clinging-microdroplet" method to fabricate patterning crystal arrays based on the employment of high-adhesion, superhydrophobic surfaces, 17 which greatly extended the scope of application.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Due to excellent self-cleaning effect, the ideal superhydrophobic surfaces with an extremely low sliding angle (SA) inspired by lotus leaf have attracted increasing attention for both fundamental research and practical applications. [4][5][6][7][8] However, some novel superhydrophobic surfaces in nature with high water adhesion, such as gecko feet, rose petals, scallions, and garlic, [9][10][11][12] have recently also attracted wide scientific interest because of their most outstanding application in no-loss microdroplet transportation known as a mechanical hand. [13][14][15][16] Especially, Jiang et al demonstrated a "clinging-microdroplet" method to fabricate patterning crystal arrays based on the employment of high-adhesion, superhydrophobic surfaces, 17 which greatly extended the scope of application.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the deposition of a colloidal dispersion of hydrophobic nanoparticles or mixtures of nanoparticles with hydrophobic molecules is a convenient method where fabrics of all types, be it cotton, polyester, lining, nylon, and so on, can be coated using dip coating or spray coating methods. A common nanoparticle of choice is SiO 2 , which is commercially available and can be also easily synthesized 10,14,25–27 . For example, Y.D.…”
Section: Introductionmentioning
confidence: 99%
“…A common nanoparticle of choice is SiO 2 , which is commercially available and can be also easily synthesized. 10,14,[25][26][27] For example, Y.D. Kim and colleagues prepared a colloidal solution by first vapor phase coating of SiO 2 nanoparticles with PDMS at 300 K for 16 h, followed by dispersing the PDMS-coated SiO 2 nanoparticles in the PDMS dispersion of hexane.…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of these studies nanostructures are generated on glass surfaces by phase-separation procedures [25,26], reactive ion-etching [27] or self-assembly methods [28]. In the light of cost reduction requirements, the sol-gel process is also described as a preferred method [29][30][31][32] where the derived structures are mostly formed by nanoparticles. Whereas numerous papers concentrate on superhydrophobic surfaces, the coating in [26] displays both, long-term superhydrophilicity and after applying a hydrophobic top coating also superhydrophobicity with low contact angle hysteresis < 3°.…”
Section: Introduction *mentioning
confidence: 99%